The Place of Culture in EFL Teaching: A Succinct Overview - HAKIMI, Mohammed; BASSAOUI, Samir; KOUMACHI, Bani (Journal of English Language Teaching and Applied Linguistics, 2024)
The incorporation of cultural elements in a foreign language (FL) classroom has been a subject of interest for many scholars over the past decades. The literature clearly demonstrates the widespread recognition of culture’s inevitable emergence in foreign language instruction. Nonetheless, there is a belief that culture should be instructed in the same way language is. Therefore, this short review provides operational definitions of culture within the field of education while shedding light on the distinction between objective culture and subjective culture. Furthermore, it explores the inseparable connection between language and culture. This paper stresses the significance of teaching culture alongside language, highlighting its natural emergence in an English as a Foreign Language (EFL) setting and the need for a purposeful and structured approach to teaching it. Moreover, the review suggests techniques and methods for instructing cultural aspects in an EFL classroom, particularly in the context of today’s interconnected world.